Update of Clown Nose-Like Lesion, a Underrecognized Manifestation of Metastatic Malignancies and Genetic Cancer Predisposition Syndromes - Zhao, Bei; Chen, Ling; Liao, Jinfeng; Xie, Zhen; Lei, Xia; Shen, Zhu (Frontiers in Medicine, 2021)
Clown nose-like lesion refers to the manifestation of a reddish or skin-colored bulge on the tip of the nose or the manifestation of bulbous tip of the nose. More and more clinical cases show that clown nose-like lesion can also be the indication of some genetic syndromes, not just the manifestation of metastatic visceral tumor as it initially proposed. However, the clinical features of clown nose-like lesion indicated by metastatic malignancies, genetic cancer predisposition syndromes or primary diseases involing the nasal tip are lacking. In this study, patients with clown nose-like lesion in our clinical practices and from published literatures were collected and reviewed. We found that clown nose-like lesions caused by metastatic malignancies including lung cancer are often solitary and more common in male (24/31) older individuals (average age 62.3, ranging 40-78 years old). In addition, they usually appear for a short time, and are prone to be misdiagnosed as primary nasal diseases, leading to a poor prognosis (all patients with data available died within 4 months). Clown nose-like lesions associated with genetic cancer predisposition syndromes usually develop at a young age (mean age 15.3) with female preference (9/10). They are accompanied by multiple-systemic involvements, including low hair volume, developmental delay, cancer predisposition or neurological diseases. They show slow development and often positive family history (6/10). These two kinds of clown nose-like lesions are often asymptomatic, which delays the diagnosis and treatment of underlying malignancies or syndromes. In brief, the term of clown nose-like lesion is underrecognized, and should be updated. Clown nose-like lesions can serve as indicators to at least three categories of clinical issues: metastatic visceral tumors, genetic syndromes, and primary diseases involing the nasal tip. Increased awareness of clinical features of updated clown nose-like lesions can alert physicians to these underlying malignancies or syndromes, render earlier detection of associated medical issues, and allow for genetic counseling of family members.